X-ray measurements on the influence of optical probes on gas–solid fluidized beds. (September 2015) - Maurer, Simon; Wagner, Evert C.; Schildhauer, Tilman J.; van Ommen, J. Ruud; Biollaz, Serge M.A.; Mudde, Robert F.
Graphical abstract: Highlights: Bubble splitting frequency was studied with and without optical probe. Nearly constant bubble size and velocity with and without employed optical probes. Permanent monitoring with optical probes is possible within certain limits.